Role of non-human primate models in accelerating research and developing countermeasures against Zika virus infection - Li, Amanda; Coffey, Lark L; Mohr, Emma L; Raper, Jessica; Chahroudi, Ann; Ausderau, Karla K; Aliota, Matthew T; Friedrich, Thomas C; Mitzey, Ann M; Koenig, Michelle R; Golos, Thaddeus G; Jaeger, Hannah K; et al. (The Lancet. Microbe, 2025)
Zika virus, a mosquito-transmitted orthoflavivirus, has become a pathogen of global health concern ever since the virus caused an epidemic in Brazil in 2015 associated with approximately 700 000 laboratory-confirmed cases of congenital microcephaly. The subsequent spread of the epidemic in 2016 resulted in a wide spectrum of congenital neurological, ophthalmological, and developmental abnormalities across the Americas, Africa, and Asia. In this context, non-human primate models have become essential tools for Zika virus research to understand the pathogenesis of congenital brain injury and perinatal complications and for developing and testing medical countermeasures such as vaccines, diagnostics, and therapeutics. Fetal brain injury has been observed across various non-human primate species and is influenced by factors such as the Zika virus strain, gestational age at inoculation, and inoculation dose and route. Miscarriages are also seen as common outcomes of first trimester Zika virus infections. This Series paper reviews the diverse non-human primate models currently used for Zika virus research to mitigate the public health effects of future Zika virus epidemics.